2018
DOI: 10.1111/imj.13717
|View full text |Cite
|
Sign up to set email alerts
|

Depression and suicide among medical practitioners in Australia

Abstract: This review will provide an overview of the prevalence of, and risk factors for, depression and suicide in medical practitioners. It will also discuss the barriers to accessing appropriate care and potential interventions for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 20 publications
4
56
0
6
Order By: Relevance
“…responsibility, rapid change within healthcare, institutional constraints such as discrimination and intimidation, lack of autonomy, low levels of support, loss of job satisfaction, low morale and the inability to attend to their personal lives. 4,7,10 Causes of work stress may vary with medical discipline: family practitioners may face increased demands on primary care coupled with shrinking resources, 7 while emergency care doctors and oncologists may suffer elements of posttraumatic stress. Furthermore, doctors facing complaints, often perceived as shameful catastrophic personal events, are at significantly increased risk of depression, anxiety and suicidal ideation.…”
Section: Depression In Doctors: a Bitter Pill To Swallow K Outhoffmentioning
confidence: 99%
See 2 more Smart Citations
“…responsibility, rapid change within healthcare, institutional constraints such as discrimination and intimidation, lack of autonomy, low levels of support, loss of job satisfaction, low morale and the inability to attend to their personal lives. 4,7,10 Causes of work stress may vary with medical discipline: family practitioners may face increased demands on primary care coupled with shrinking resources, 7 while emergency care doctors and oncologists may suffer elements of posttraumatic stress. Furthermore, doctors facing complaints, often perceived as shameful catastrophic personal events, are at significantly increased risk of depression, anxiety and suicidal ideation.…”
Section: Depression In Doctors: a Bitter Pill To Swallow K Outhoffmentioning
confidence: 99%
“…3 Recent meta-analyses of global studies estimate an overall prevalence of 27% in medical students, 29% in registrars and up to 60% in practising doctors. 4 These figures differ widely between countries and specialties. For instance, a Cape Town study using a self-administered Beck's Depression Inventory revealed clinically relevant moderate to severe depression in 30% of public primary healthcare doctors, 5 while an Australian study found that 18% of medical students and 21% of doctors had previously been diagnosed with depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Additionally, research suggests that doctors are at elevated risk of depression and suicide compared to the general population and other professions. 3 Doctors working in rural areas also face further risks in the form of a lack of access to appropriate mental health support within their geographic area, and low availability of professionals and support services that would be confidential or sufficiently removed from their professional network. 4 Fortunately, there is evidence that burnout can be reduced by providing health professionals with skills to help manage emotional responses at work.…”
Section: Introductionmentioning
confidence: 99%
“…However physicians have access to prescription medications, and they tend to auto-medicate themselves. Drug overdose is the most common suicide method, and is used signi cantly more often by physicians than the general population [22]. Physicians have a greater risk for suicide, and depression is one of the major risk factors [23].…”
Section: Discussionmentioning
confidence: 99%